2008
DOI: 10.1088/0957-0233/19/10/102001
|View full text |Cite
|
Sign up to set email alerts
|

Silicon carbide and its use as a radiation detector material

Abstract: We present a comprehensive review of the properties of the epitaxial 4H silicon carbide polytype (4H-SiC). Particular emphasis is placed on those aspects of this material related to room, high-temperature and harsh environment ionizing radiation detector operation. A review of the characterization methods and electrical contacting issues and how these are related to detector performance is presented. The most recent data on charge transport parameters across the Schottky barrier and how these are related to ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
179
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 261 publications
(189 citation statements)
references
References 138 publications
2
179
0
Order By: Relevance
“…A similar defect level has been attributed to the silicon vacancy [24], carbon vacancy, split interstitial or antisites after low energy electron irradiation [25]. It was observed that defect E 0.39 disappeared after leaving the sample at room temperature for a week, showing that the defect was not stable at room temperature.…”
Section: Deep Level Transient Spectroscopy Analysissupporting
confidence: 54%
“…A similar defect level has been attributed to the silicon vacancy [24], carbon vacancy, split interstitial or antisites after low energy electron irradiation [25]. It was observed that defect E 0.39 disappeared after leaving the sample at room temperature for a week, showing that the defect was not stable at room temperature.…”
Section: Deep Level Transient Spectroscopy Analysissupporting
confidence: 54%
“…Silicon is the workhorse for information technologies and photovoltaic photon harvesting, while SiC is a promising material for high power, high temperature and high frequency applications, because of its extreme thermal and chemical stability together with the large electron saturation velocity and mobility [3,4] and SiC has applications in light-emitting diodes [2][3][4], temperature sensors [5] and as neutron detectors [6,7]. The most stable of about 100 different SiC polytypes, the hexagonal 6H-SiC containing six SiC pairs per unit cell with the stacking sequence ABCACB [8] is the subject of this study.…”
Section: Introductionmentioning
confidence: 99%
“…Most suitable semiconductors for harsh environment applications are Silicon-Carbide (SiC) and diamond thanks to their high atomic displacement energy, which is about 20-35 eV [1] for SiC and 40-50 eV [2] for diamond. The high displacement threshold energy makes them more radiation resistant than the conventional semiconductors such as Silicone (Si), Germanium (Ge) and Gallium Arsenide (GaAs) [3]. Moreover, the wide-bandgap energy and low intrinsic carrier concentration over considerable range of temperature make SiC and diamond interesting for use at high temperature applications.…”
Section: Introductionmentioning
confidence: 99%